The Correlation Of Cognitive And Memory With Pragmatic Ability In Older People - Mangunsong, Roy Romey Daulas; Sudarman, Sudarman (Jurnal Keterapian Fisik, 2023)
Background: Older people experience decreased cognitive abilities, decreased memory, confusion, and difficulty understanding what others say and how they use language. The elderly often have conversations that are not fluent and are difficult to listen to. Decreasing speed in processing information and decreasing working memory, especially in terms of the ability to store information in the mind when processing, tend to contribute to a lack of language efficiency in the elderly. This study aimed to determine the relationship between cognitive, memory, and pragmatic abilities in Surakarta's older people. Methods: This study uses a cross-sectional approach to quantitative research with an observational analytical plan. The sample consisted of 30 respondents living in Surakarta. Bivariate analysis using standard deviation and multivariate analysis using logistic linear regression models. The research instruments used were cognitive-linguistic evaluation, memory examination, and the assessment of pragmatic skills. Results: The effect of statistical tests with contingency coefficient tests showed that cognitive ability and memory ability affected the pragmatic ability of older people with a p-value of 0.000, 0.01, and a correlation coefficient value of 0.550, 0.531. Meanwhile, the multivariate test using logistic regression results showed a value of sig.0.003<0.05. Conclusion: There is a relationship between cognitive and memory ability with the pragmatic ability of older people in Surakarta.